2022
DOI: 10.1097/qad.0000000000003405
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus disease 2019 vaccine effectiveness among a population-based cohort of people living with HIV

Abstract: Objective:People with HIV were underrepresented in coronavirus disease 2019 (COVID-19) vaccine clinical trials. We estimated vaccine effectiveness (VE) against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection for the BNT162b2, mRNA-1273, and ChAdOx1 vaccines among a population-based cohort of people with HIV in Ontario, Canada.Design:Test-negative designMethods:We identified people with HIV aged ≥19 years who were tested for SARS-CoV-2 by RT-PCR between December 14, 2020 (first availabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…These studies may include, at this point, effectiveness studies focusing on PWH, which may justify the use of strategies such as additional doses of the vaccine or heterologous boosting. Future research should also investigate the effectiveness of vaccines among PWH who have higher levels of immunodeficiency and PWH against Omicron or future variants [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…These studies may include, at this point, effectiveness studies focusing on PWH, which may justify the use of strategies such as additional doses of the vaccine or heterologous boosting. Future research should also investigate the effectiveness of vaccines among PWH who have higher levels of immunodeficiency and PWH against Omicron or future variants [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…We would like to discuss ‘COVID-19 Vaccine Effectiveness among a Population-based Cohort of People Living with HIV’ [1]. In a population-based cohort of HIV-positive individuals in Ontario, Canada, Chambers et al [1] calculated the vaccination efficacy against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection for the BNT162b2, mRNA-1273, and ChAdOx1 vaccines. Prior to the development of the Omicron version, Chambers et al [1] found that two doses of the COVID-19 vaccine provided significant protection against clinical illness and hospitalization/death in HIV-positive individuals.…”
mentioning
confidence: 99%
“…In a population-based cohort of HIV-positive individuals in Ontario, Canada, Chambers et al [1] calculated the vaccination efficacy against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection for the BNT162b2, mRNA-1273, and ChAdOx1 vaccines. Prior to the development of the Omicron version, Chambers et al [1] found that two doses of the COVID-19 vaccine provided significant protection against clinical illness and hospitalization/death in HIV-positive individuals. A generalization that coronavirus disease 2019 (COVID-19) vaccination efficacy is lower among HIV-positive individuals in communities that, for the most part, are attending HIV care, taking antiretroviral medicine, and are virally suppressed is not supported by the findings, according to Chambers et al [1].…”
mentioning
confidence: 99%
See 2 more Smart Citations